KEBERTAHANAN KOSAKATA BAHASA CIACIA DALAM TRADISI MA’ATA’A PADA MASYARAKAT DESA GUNUNG SEJUK - Farni Gafar; sulfiah; Rachman (Jurnal Bastra (Bahasa dan Sastra), 2026)
The research aims to determine the level of lexical retention of the Ciacia language within the ma’ata’a traditional ceremony in Gunung Sejuk Village, Sampolawa District, Buton Selatan Regency. The type of research used is field research employing a quantitative method to describe the degree of vocabulary retention. The data were collected through questionnaires. The results of the study indicate that from 100 lexical items presented to 50 respondents, a total of 5.000 lexical data were obtained. Of these, 2.041 vocabularies (40,82%) are still known and actively used, 1.791 vocabularies (35,82%) are known but no longer used, and 1.181 vocabularies (23,62%) are neither known nor used by the respondents. Based on these findings, it can be concluded that the lexical retention of the Ciacia language in the ma’ata’a traditional ceremony among the people of Gunung Sejuk Village can still be maintained, with a retention rate of 40,82%.